2015
DOI: 10.1016/j.ijgo.2015.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Profiling maternal plasma microRNA expression in early pregnancy to predict gestational diabetes mellitus

Abstract: The five miRNAs that were differentially expressed in GDM could serve as noninvasive biomarkers. The results also provide insights into the molecular mechanisms that underlie GDM, thereby contributing to the diagnosis and treatment of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
175
4
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(193 citation statements)
references
References 26 publications
12
175
4
2
Order By: Relevance
“…Measurement of serum PlGF at 11-14 weeks improves the performance of early screening for GDM (Eleft heriades et al 2014). Yilmaz and colleagues have suggested also the neutrophil-to-lym-phocyte ratio (NLR) as an independent predictor of GDM development (Zhu et al 2015). Finally, in the next future, miRNA expressed in GDM could serve as earlier predictive markers (Zhu et al 2015).…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Measurement of serum PlGF at 11-14 weeks improves the performance of early screening for GDM (Eleft heriades et al 2014). Yilmaz and colleagues have suggested also the neutrophil-to-lym-phocyte ratio (NLR) as an independent predictor of GDM development (Zhu et al 2015). Finally, in the next future, miRNA expressed in GDM could serve as earlier predictive markers (Zhu et al 2015).…”
Section: Diagnosismentioning
confidence: 99%
“…Yilmaz and colleagues have suggested also the neutrophil-to-lym-phocyte ratio (NLR) as an independent predictor of GDM development (Zhu et al 2015). Finally, in the next future, miRNA expressed in GDM could serve as earlier predictive markers (Zhu et al 2015). In particular, Dicer and Drosha are the two major enzymes in the miRNA biogenesis process with evidence of up-regulation in GDM patients (Rahimi et al 2015).…”
Section: Diagnosismentioning
confidence: 99%
“…‱ Association between levels of some miRNAs and markers of microvascular impairment revealed the dysregulation of some in the serum and plasma of women who went on to develop GDM compared with the controls [43,44]. These results suggest that circulating miRNAs could be used as biomarkers for the early diagnosis or as a predictive factor for GDM.…”
Section: Circulating Mirnas As Early Predictive Biomarkers Of Diabetesmentioning
confidence: 89%
“…Furthermore, the miRNA content of different types of blood cells were also deregulated in type 1 and type 2 diabetic patients compared with controls [38][39][40][41][42]. Finally, analysis of circulating miRNAs in women with gestational diabetes mellitus has revealed that in both serum and plasma some miRNAs have an altered profile compared with those in control women [43,44].…”
Section: Circulating Mirnas As Biomarkers Of the Diabetic Conditionmentioning
confidence: 95%
“…A kezelĂ©s korai megkezdĂ©se megelƑzheti a szövƑdmĂ©nyek kialakulĂĄsĂĄt. Erre alkalmasak a miRNSmolekulĂĄk, amelyek anyai vĂ©rbƑl mĂĄr a 12. hĂ©ten kimutatĂłk, pĂ©ldĂĄul a miR- 16, miR-17, miR-19a, miR-19b Ă©s miR-20 [26].…”
Section: A Mirnsunclassified